2018
DOI: 10.31786/09756272.18.9.2.206
|View full text |Cite
|
Sign up to set email alerts
|

Water Scarcity in India: A Threat to Sustainable Management of Water

Abstract: Water is life for all the living organisms which is present on earth. Water is needed to ensure food security, feed livestock, and take up industrial production and to conserve the environment. Water scarcity involves water stress, water shortage or deficits, and water crisis. This may be due to both nature and humans. Main factors that contribute to this issue include poor management of resources, lack of government attention, awareness and anthropogenic waste. The increased value of solid wastes and other ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…India is highly populated and despite its economic growth it failed to achieve the target set in MDG regarding the reduction of hunger [78]. The problem of food security in India will be worsened by climate change because of water scarcity and droughts [79,80]. The current study also showed that publications from the UK had the highest number of citations per document.…”
Section: Discussionmentioning
confidence: 67%
“…India is highly populated and despite its economic growth it failed to achieve the target set in MDG regarding the reduction of hunger [78]. The problem of food security in India will be worsened by climate change because of water scarcity and droughts [79,80]. The current study also showed that publications from the UK had the highest number of citations per document.…”
Section: Discussionmentioning
confidence: 67%
“…In the recent past, many cities faced imminent threat of water scarcity which includes cities like Delhi, Bengaluru, Hyderabad, Shimlaetc. Latur District of Marathwara region in Maharastra witnessed severe water crisis because of drought and has taken the lives of many farmers (Rana and Guleria, 2018).…”
Section: Projected Patterns Of Precipitation Changesmentioning
confidence: 99%
“…Conservation strategies of India:-Indian legal system provides man laws for addressing the problem of water pollution thus promotes its conservation. by NITI Aayog as a useful tool to assess and improve the performance in efficient management of water resources (Rana and Guleria, 2018).…”
Section: Climate Change Impact On Water Resources and Food Security-mentioning
confidence: 99%
“…The quantity of this utilizable water is very limited on Earth. Most of India's surface waters, including rivers and lakes, are getting increasingly polluted due to the onslaught of human activities of diverse nature (Rana & Guleria, 2018). "Our observation focused on the methods these individuals employed to sustain themselves.…”
Section: Introductionmentioning
confidence: 99%